Advanced periodic maintenance scheduling methods for aircraft lifecycle management - Fedotova, Alena; Taratoukhine, Victor; Ovsyannikov, Mikhail (Cranfield University Press, 2013)
This paper reviews existing methods and techniques addressing the problem of maintenance support throughout the life cycle for high value manufacturing products such as aircrafts. As part of this doctorate research the analysis of current methods of maintenance scheduling was conducted. In order to contribute to a more comprehensive solution, an advanced approach (algorithm) of periodic maintenance is presented. The authors believe that this approach will reduce the cost of maintenance of high value manufacturing products. The algorithm based on constraint programming methods is briefly presented and the future research directions are discussed.
Keywords: Information systems; maintenance and repair of equipment; maintenance cost; periodic maintenance scheduling methods; domain ontology; methods of constraint satisfaction problem